Evaluating dried salted cod amino acid signature for nutritional quality assessment and discriminant analysis - Quaresma, M. A. G.; Pereira, G.; Nunes, M. L.; Sponda, C.; Jardim, A.; Gonçalves, H.; Santos, C.; Roseiro, L. C. (Frontiers in Nutrition, 2023)
Aim Thus, the aim of this study was to answer three scientific questions: (1) Are the protein content and amino acid profile of dried salted cod influenced by species (Gadus morhua and Gadus macrocephalus)? (2) Are the protein content and amino acid profile of dried salted cod influenced by the geographical area of capture (Iceland and Norway)? and (3) Does the amino acid profile have the potential to be used as a discriminator of species and geographical areas of capture? Methods A total of 45 dried salted cods (2–3 kg of dry weight; n = 15 samples/origin) were used in this study. The Atlantic cod was fished in the Atlantic northeast (FAO 27 area) within the Exclusive Economic zones (EEZ) of Norway (n = 15) and Iceland (n = 15), while the Pacific cod was caught in the Pacific northeast (FAO 67 area) within the Alaska EEZ (n = 15). Total protein content was determined by the Kjeldahl method, in accordance with the AOAC procedures. The amino acid profile was analyzed by HPLC with fluorescence detection (at excitation and emission wavelengths of 338 and 425 nm, respectively). Results The Atlantic cod presented higher contents of total protein (33.90 versus 33.10 g/100 g of cod edible portion; p = 0.017) and total amino acid contents (32.52 versus 32.04 g/100 g of cod edible portion; p = 0.015) but displayed lower percentage of indispensable amino acids (32.16 versus 32.83 g/100 g of protein; p < 0.001) than Pacific cod. Among the Atlantic cod harvesting locations, the Norwegian cod displayed higher total amino acid contents (96.91 versus 96.81 g/100 g of protein; p = 0.012) and higher percentage of indispensable amino acids (35.38 versus 28.94 g/100 g of protein; p = 0.042) than the Icelandic counterpart. A correct classification of 100% was obtained for the Pacific and Icelandic cod varieties, but the classification accuracy in the Norwegian cod was of just 86.67%, since 2 samples out of 15 were incorrectly classified as Icelandic. Conclusion The comparison of cod species showed that the Atlantic cod had a significantly lower EAAI than the Pacific cod (p < 0.001; 88.23 versus 88.61). On the other hand, the comparison of the two origins in the Atlantic cod, showed that Norwegian cod displayed a significantly higher EAAI than the Icelandic cod (99.15 versus 77.32). The assessment of the EAAI allows the classification of the protein’s nutritional quality, allowing us to classify both cod species as a good protein source to human diet. However, within the Atlantic cod, the Norwegian cod’s protein is classified as high quality, while the Icelandic cod attain the classification of useful quality. Regarding the amino acid profile discriminatory potential to classify cod samples. The results show that the AA profile has 100% accuracy in the separation of cod species, but was not globally efficient in the differentiation of the Norwegian from the Icelandic cod.